(untitled) (Baghdad Science Journal, 2025)
Recording two species of larval cestodes Callitetrarhynchus gracilis and Callitetrarhynchus sp. (Cestoda: Trypanorhyncha) parasitic in body cavity of two carangid fishes (Carangoides malabaricus and Megalaspis cordyla) from north west Arab Gulf, Iraq, is described. The species Callitetrarhynchus sp. was recorded for the first time in Iraq in carangid fishes. Also, two fish species (C. malabaricus and M. cordyla) are considered as new hosts for C. gracilis and Callitetrarhynchus sp. in the Arab Gulf. The cestodes were sent to Prof. Dr. Harry W. Palm, Department of Fisheries Biology, Institute Zoo Morphology, Germany for confirmation of the identification.